The Role of Cooperatives in Improving Farmer Welfare in the Era of Food Security - Massenga, Talitha Wenifrida (Indonesian Journal of Research and Service Studies, 2024)
Food security is one of the strategic issues that places cooperatives as important institutions in supporting increased farmer welfare and sustainable agricultural development. This research aims to comprehensively analyze the role of cooperatives in improving farmers' welfare in the era of food security. The research uses the Literature Review (Library Research) method by synthesizing reputable scientific literature and relevant policy documents. The research results show four main findings, namely that cooperatives play a role in improving farmers' economic welfare, expanding access to markets, financing and innovation, encouraging institutional transformation towards digital and sustainable agriculture, and strengthening food security through stabilizing food production, distribution and access. This research concludes that the effectiveness of cooperatives is determined by the quality of governance, institutional capacity, digital transformation and multi-stakeholder collaboration so that strengthening cooperatives is an important strategy in realizing farmer welfare and sustainable food security.